The Urgency of Developing Youth Career Resilience Through Guidance and Counseling as an Effort to Prepare for the Golden Generation 2045 - Mohamad Saripudin; Yaya Sunarya; Evi Afiati; Rahmawati Rahmawati (Indonesian Journal of Educational Counseling, 2022)
This article aims to 1) examine youth career resilience as an important competency to face the year 2045; 2) assess the urgency of developing career resilience through guidance and counseling as an effort to prepare adolescents to become the golden generation of 2045. From the results of the study, it is known that 1) the golden generation of 2045 who has high career resilience will be able to face a borderless society, global urbanization, and international trade; 2) Through guidance and counseling services, career resilience can be developed from the age of adolescent development, with focus on developing career resilience attributes.